Self-Service Technology Service Quality and Brand Loyalty in Zimbabwe’s Banking Sector: A SEM Approach: Array - Maune, Alexander (Acta Universitatis Danubius. Œconomica, 2022)
Purpose – This article examined the relationship between self-service technology service quality and brand loyalty in Zimbabwe`s banking sector with customer satisfaction and behaviour intentions playing the mediating role. The main objective was to develop a path analysis model for the banking industry in Zimbabwe. Approach – The study followed a deductive approach with an online survey used to collect primary data from more than 110 bank customers. The PLS-SEM algorithm was used to empirically test the path analysis model. Findings – The construct measures were confirmed reliable and valid with structural model showing goodness of fit based on the R2, Q2, SRMR, and path significance. The results further confirmed hypothesis H1, H2, H3, H4, and H7 whilst rejecting H5 and H6. Practical implications – Self-service technologies have proven to be a critical enhancer of brand loyalty in the banking sector. The ‘FinTech’ industry has gone under a critical test due to COVID-19 pandemic that has seen global restrictions nearly paralyzing a number of sectors. Technology developers, policymakers, researchers, and regulators will have a better understanding of self-service technologies and their impact on brand loyalty in the service industry. Originality/value – Literature has shown some knowledge gaps in this field especially in Zimbabwe where the ‘FinTech’ industry is still in its infancy stages.